Learning Organization Leadership and Competitive Advantage in Madrasahs: A Conceptual Business Strategy Approach - Mukhamad Ilyasin; Akhmad Muadin (Faculty of Education and Teacher Training of UINSI Samarinda, 2025)
This study examines the role of learning organization leadership in creating the competitive advantage of madrasahs through a business strategy approach. The study is grounded in the assumption that madrasahs, as Islamic educational institutions, are required to respond to globalization, intensifying competition, and increasing public expectations by strengthening both organizational learning and strategic management. A qualitative design with an exploratory case study approach was employed to investigate madrasahs that had implemented learning organization leadership and demonstrated competitive advantage. Data were collected through interviews, observations, and document analysis and were analyzed using qualitative data analysis supported by triangulation to ensure trustworthiness. The findings reveal that learning organization leadership is characterized by a clear and measurable vision, a strong commitment to continuous learning and professional development, the cultivation of a collaborative learning culture, effective teamwork, openness to change, and encouragement of innovation. These leadership characteristics enable madrasahs to formulate adaptive business strategies aimed at improving learning quality, strengthening service quality, enhancing institutional competitiveness, attracting prospective students, and increasing public trust. The study also shows a functional relationship in which learning organization leadership serves as the enabling force, business strategy acts as the value-creation mechanism, and competitive advantage emerges as the organizational outcome. In conclusion, the study highlights that visionary, adaptive, and stakeholder-oriented leadership is essential for sustaining the relevance, legitimacy, and competitiveness of madrasahs in a rapidly changing educational environment.